Dilema Etis Profesi Akuntan Berdasarkan Aspek Keperilakuan - Widyari, Nyoman Yudha Astriayu; Sari, Ida Ayu Komang Tiara Pratistha; Putri, Putu Ayu Diah Widari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2024)
The article discusses ethical dilemmas in the accounting profession, focusing on behavioral aspects. The paper highlights the importance of ethics as a foundational component for responsible societies and sustainable development, especially within professions like accounting that rely heavily on ethical standards. It explores the complexities accountants face in maintaining objectivity, independence, confidentiality, integrity, and professional prudence. By reviewing literature and theories such as agency theory, positive accounting theory, and compliance theory, the study delves into ethical conflicts that arise due to pressures from stakeholders and organizational demands. The article emphasizes the role of ethical sensitivity and decision-making, especially in situations where external pressures can compromise ethical conduct. The authors advocate for ethical standards and decision-making frameworks that help accountants navigate ethical dilemas, ensuring reliable and transparent financial reporting.